We will learn how to find the sum of n terms of the Geometric Progression {a, ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ...........}
To prove that the sum of first n terms of the Geometric Progression whose first term ‘a’ and common ratio ‘r’ is given by
S\(_{n}\) = a(\(\frac{r^{n} - 1}{r - 1}\))
⇒ S\(_{n}\) = a(\(\frac{1 - r^{n}}{1 - r}\)), r ≠ 1.
Let Sn denote the sum of n terms of the Geometric Progression {a, ar, ar\(^{2}\), ar\(^{3}\), ar\(^{4}\), ...........} with first term ‘a’ and common ratio r. Then,
Now, the nth terms of the given Geometric Progression = a ∙ r\(^{n - 1}\).
Therefore, S\(_{n}\) = a + ar + ar\(^{2}\) + ar\(^{3}\) + ar\(^{4}\) + ............... + ar\(^{n - 2}\) + ar\(^{n - 1}\) ............ (i)
Multiplying both sides by r, we get,
rS\(_{n}\) = ar + ar\(^{2}\) + ar\(^{3}\) + ar\(^{4}\) + ar\(^{4}\) + ................ + ar\(^{n - 1}\) + ar\(^{n}\) ............ (ii)
____________________________________________________________
On subtracting (ii) from (i), we get
S\(_{n}\) - rS\(_{n}\) = a - ar\(^{n}\)
⇒ S\(_{n}\)(1 - r) = a(1 - r\(^{n}\))
⇒ S\(_{n}\) = a\(\frac{(1 - r^{n})}{(1 - r)}\)
⇒ S\(_{n}\) = a\(\frac{(r^{n} - 1)}{(r - 1)}\)
Hence, S\(_{n}\) = a\(\frac{(1 - r^{n})}{(1 - r)}\) or, S\(_{n}\) = a\(\frac{(r^{n} - 1)}{(r - 1)}\)
Notes:
(i) The above formulas do not hold for r = 1. For r = 1, the sum of n terms of the Geometric Progression is S\(_{n}\) = na.
(ii)When the numerical value of r is less than 1 (i.e., - 1 < r < 1), then the formula S\(_{n}\) = a\(\frac{(1 - r^{n})}{(1 - r)}\) is used.
(iii) When the numerical value of r is greater than 1 (i.e., r > 1 or, r < -1) then the formula S\(_{n}\) = a\(\frac{(r^{n} - 1)}{(r - 1)}\) is used.
(iv) When r = 1, then S\(_{n}\) = a + a + a + a + a + .................... to n terms = na.
(v) If l is the last term of the Geometric Progression, then l = ar\(^{n - 1}\).
Therefore, S\(_{n}\) = a(\(\frac{1 - r^{n}}{1 - r}\)) = (\(\frac{a - ar^{n}}{1 - r}\)) = \(\frac{a - (ar^{n - 1})r}{(1 - r)}\) = \(\frac{a - lr}{1 - r}\)
Thus, S\(_{n}\) = \(\frac{a - lr}{1 - r}\)
Or, S\(_{n}\) = \(\frac{lr - a}{r - 1}\), r ≠ 1.
Solved examples to find the Sum of first n terms of the Geometric Progression:
1. Find the sum of the geometric series:
4 - 12 + 36 - 108 + .............. to 10 terms
Solution:
The first term of the given Geometric Progression = a = 4 and its common ratio = r = \(\frac{-12}{4}\) = -3.
Therefore, the sum of the first 10 terms of the geometric series
= a ∙ \(\frac{r^{n} - 1}{r - 1}\), [Using the formula S\(_{n}\) = a\(\frac{(r^{n} - 1)}{(r - 1)}\) since, r = - 3 i.e., r < -1]
= 4 ∙ \(\frac{(-3)^{10} - 1}{-3 - 1}\)
= 4 ∙ \(\frac{(-3)^{10} - 1}{-4}\)
= - (-3)\(^{10}\) - 1
= -59048
2. Find the sum of the geometric series:
1 + \(\frac{1}{2}\) + \(\frac{1}{4}\) + \(\frac{1}{8}\) + \(\frac{1}{16}\) + .............. to 10 terms
Solution:
The first term of the given Geometric Progression = a = 1 and its common ratio = r = \(\frac{\frac{1}{2}}{1}\) = \(\frac{1}{2}\)
Therefore, the sum of the first 10 terms of the geometric series
S\(_{10}\) = a\(\frac{(1 - r^{10})}{(1 - r)}\)
⇒ S\(_{10}\) = 1 ∙ \(\frac{(1 - (\frac{1}{2})^{10})}{(1 - \frac{1}{2})}\)
⇒ S\(_{10}\) = 2(\(\frac{1}{2^{10}}\))
⇒ S\(_{10}\) = 2(\(\frac{2^{10} - 1}{2^{10}}\))
⇒ S\(_{10}\) = 2(\(\frac{1024 - 1}{1024}\))
⇒ S\(_{10}\) = \(\frac{1024 - 1}{512}\)
⇒ S\(_{10}\) = \(\frac{1023}{512}\)
Note that we have used formula Sn = a(\(\frac{(1 - r^{n})}{(1 - r)}\) since r = 1/4 i.e., r < 1]
3. Find the sum of 12 terms of the Geometric Progression 3, 12, 48, 192, 768, ................
Solution:
The first term of the given Geometric Progression = a = 3 and its common ratio = r = \(\frac{12}{3}\) = 4
Therefore, the sum of the first 12 terms of the geometric series
Therefore, S\(_{12}\) = a\(\frac{r^{12} - 1}{r - 1}\)
= 3(\(\frac{4^{12} - 1}{4 - 1}\))
= 3(\(\frac{16777216 - 1}{3}\))
= 16777216 - 1
= 16777215
4. Find the sum to n terms: 5 + 55 + 555 + 5555 + .............
Solution:
We have 5 + 55 + 555 + 5555 + ............. to n terms
= 5[1 + 11 + 111 + 1111 + .............. + to n terms]
= \(\frac{5}{9}\)[9 + 99 + 999 + 9999 + ................ + to n terms]
= \(\frac{5}{9}\)[(10 – 1) + (10\(^{2}\) - 1) + (10\(^{3}\) - 1) + (10\(^{4}\) - 1) + .............. + (10\(^{n}\) - 1)]
= \(\frac{5}{9}\)[(10 + 10\(^{2}\) + 10\(^{3}\) + 10\(^{4}\) + ................ + 10\(^{n}\)) – ( 1 + 1 + 1 + 1 + ................ + 1)] n times
= \(\frac{5}{9}\)[10 × \(\frac{(10^{n} - 1)}{(10 - 1)}\) – n]
= \(\frac{5}{9}\)[\(\frac{10}{9}\)(10\(^{n}\) – 1) – n]
= \(\frac{5}{81}\)[10\(^{n + 1}\) – 10 – 9n]
● Geometric Progression
11 and 12 Grade Math
From Sum of n terms of a Geometric Progression to HOME PAGE
Didn't find what you were looking for? Or want to know more information about Math Only Math. Use this Google Search to find what you need.
Apr 18, 24 02:58 AM
Apr 18, 24 02:15 AM
Apr 18, 24 01:36 AM
Apr 18, 24 12:31 AM
Apr 17, 24 01:32 PM